Coastal Subsistence, Maritime Trade, and the Colonization of Small Offshore Islands in Eastern African Prehistory. (3rd May 2016) - Crowther, Alison; Faulkner, Patrick; Prendergast, Mary E.; Quintana Morales, Eréndira M.; Horton, Mark; Wilmsen, Edwin; Kotarba-Morley, Anna M.; Christie, Annalisa; Petek, Nik; Tibesasa, Ruth; Douka, Katerina; Picornell-Gelabert, Llorenç; et al.
ABSTRACT: Recent archaeological research has firmly established eastern Africa's offshore islands as important localities for understanding the region's pre-Swahili maritime adaptations and early Indian Ocean trade connections. While the importance of the sea and small offshore islands to the development of urbanized and mercantile Swahili societies has long been recognized, the formative stages of island colonization—and in particular the processes by which migrating Iron Age groups essentially became "maritime"—are still relatively poorly understood. Here we present the results of recent archaeological fieldwork in the Mafia Archipelago, which aims to understand these early adaptations and situate them within a longer-term trajectory of island settlement and pre-Swahili cultural developments. We focus on the results of zooarchaeological, archaeobotanical, and material culture studies relating to early subsistence and trade on this island to explore the changing significance of marine resources to the local economy. We also discuss the implications of these maritime adaptations for the development of local and long-distance Indian Ocean trade networks.